Flag Ceremony From the Perspective of Grade IV Students at Sukarasa State Elementary School - Syakira Hanifa; Muh Husen Arifin (CV. Rayyan Dwi Bharata, 2023)
The flag ceremony is proof that our country always appreciates the services of heroes who have fought for independence. As Indonesian citizens, it is our duty to follow it solemnly and voluntarily, including all students in Indonesia. Students should be able to interpret and know the purpose of holding a flag ceremony so that they can carry out the flag ceremony solemnly and voluntarily as a form of character development. However, not a few students joked, chatted in line, and made moves that shouldn't have been done. Therefore, after conducting research they only participate in ceremonial activities without knowing the meaning of the flag ceremony. Therefore, all school members need to work together to build a spirit of nationalism and love for the homeland in students, as a form of character development through flag ceremony activities.